The Effectiveness of Dysmenorrhea and Lemon Aromatherapy Gymnastics on the Pain Level Score and Frequency of Dysmenorrhea Events in Young Women of Jatibening Village in 2023: Efektivitas Senam Dismenore dan Aromaterapi Lemon Terhadap Skor Tingkat Nyeri dan Frekuensi Kejadian Dismenore pada Remaja Putri Kelurahan Jatibening Tahun 2023 - Elisabeth Petege; Wintarsih (Prodi Kebidanan Universitas Islam Negeri Alauddin Makassar, 2023)
Introduction Dysmenorrhea is a disorder of the female reproductive organs that is felt during menstruation which has an impact on disruption of daily activities, the symptoms are pain in the lower abdominal area to the waist and requires treatment. Method The research design using Quasy Experiment with Pre and Post Design approaches and the relationship between the two variables was tested using the dependent data analysis technique Paired T-test. Sampling was carried out by random sampling technique as many as 36 respondents. The research instrument uses sheets to measure the NRS (Numeric Rating Scale) pain scale. Result The results of the Wilcoxon test in the intervention group for dysmenorrhea and lemon (Cytrus) aromatherapy obtained a sig. (2-tailed) is 0.000 < 0.05. The average dysmenorrhea pain level scale in the pre-test intervention group was 5.69 (moderate pain) and in the post-test intervention group was 1.31 (mild pain). The difference between pre-test and post-test pain was 4.38. Conclusion There is a significant effect between dysmenorrhea gymnastics and lemon (Cytrus) aromatherapy on reducing the intensity of dysmenorrhea pain levels.